Pengembangan Majalah Elektronik Berbasis Aplikasi Anyflip Pada Materi Sel Untuk Siswa Kelas XI SMA/MA - Lestari, Lidya Cindy; Sari, Tika Mayang (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
The results of a pre-survey at SMA Negeri 1 Kotagajah found several problems, namely only about 50% of students in the class focused on taking biology lessons. According to the biology teacher, the lack of focus during learning is influenced by several factors, one of which is a non-motivating learning resource. Biology teachers experience difficulties in teaching cell material because the teaching materials used do not cover material clearly and completely. During learning activities, the media used is minimal in cell material. The teaching materials used are only printed books and power points. Therefore, it is necessary to develop an electronic magazine based on the Anyflip application. This study aims to develop an electronic magazine based on the Anyflip application as a learning medium for class XI student at Senior High School. This research includes Research and Development, research using the ADDIE model. The results of product validation and testing show that the electronic magazine based on the Anyflip application as a learning medium for class XI SMA/MA students is “Very Good” and is feasible to use. This is obtained based on the percentage of product validation and trial results. The percentage results obtained for each were subject matter experts by 81%, media experts by 96%, teacher responses by 96%, students responses by 89%, and all results were categorized as